Risk of all-cause and cause-specific mortality associated with immune-mediated inflammatory diseases in Korea - Kwon, Oh Chan; Lee, See Young; Chun, Jaeyoung; Han, Kyungdo; Kim, Yuna; Kim, Ryul; Park, Min-Chan; Kim, Jie-Hyun; Youn, Young Hoon; Park, Hyojin (Frontiers in Medicine, 2023)
Objective: Immune-mediated inflammatory disease (IMID) is associated with an increased risk of mortality. It is unclear whether the higher mortality is attributable to the IMIDs themselves or to the higher prevalence of comorbidities in IMIDs. We aimed to investigate whether IMIDs per se confer a higher risk of mortality. Methods: From the Korean National Health Insurance Service-National Sample Cohort database, this population-based cohort study included 25,736 patients newly diagnosed with IMIDs between January 2007 and December 2017, and 128,680 individuals without IMIDs who were matched for age, sex, income, hypertension, type 2 diabetes, dyslipidemia, and the Charlson comorbidity index. All individuals were retrospectively observed through December 31, 2019. The outcomes included all-cause and cause-specific mortalities. Adjustments for age, sex, and comorbidities were performed using multivariable Cox proportional hazard regression analyses, and adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) for the outcomes were estimated. Results: The adjusted risk of all-cause mortality was significantly lower in patients with IMIDs than that in those without (aHR, 0.890; 95% CI, 0.841–0.942). Regarding cause-specific mortality, cancer-specific (aHR, 0.788; 95% CI, 0.712–0.872) and cardiovascular disease-specific (aHR, 0.798; 95% CI, 0.701–0.908) mortalities were the two causes of death that showed significantly lower risks in patients with IMIDs. A similar trend was observed when organ based IMIDs were analyzed separately (i.e., gut, joint, and skin IMIDs). Conclusion: After adjusting for comorbidities, IMIDs were associated with a lower risk of all-cause mortality compared to those without IMIDs. This was attributable to the lower risks of cancer- and cardiovascular disease-specific mortalities.